Locally advanced anorectal malignant melanoma in septuagenarian patient treated by laparoscopic abdominoperineal resection: A case report. (October 2021) - Futori, Takuya; Enomoto, Tsuyoshi; Owada, Yohei; Ohara, Yusuke; Matsumura, Hideki; Oda, Tatsuya
Abstract: Introduction: Anorectal malignant melanoma (ARMM) is a rare disease with a poor prognosis. In cases involving locally advanced disease, the treatment strategy is difficult, especially in octogenarian patients, because the prognosis is poor, despite the corresponding decrease or loss of the anal function. Presentation of case: A 78-year-old woman was admitted to a local hospital with chief complaints of severe anal discomfort due to an egg-sized tumor that was protruding out of the anus and melena. A diagnosis of ARMM was confirmed based on the examination of biopsy specimens and imaging study showed swollen lymph nodes on the dorsal side of the middle rectum and left internal iliac lymph nodes. Laparoscopic abdominoperineal resection with left lateral lymph node dissection was performed. The examination of the resected specimen revealed two polypoid tumors with a maximum diameter of 38 mm and 14 mm with a metastatic lymph node of 62 mm in the mesorectum. The postoperative course was uneventful. Relapse and local recurrence free survival without any complaints was obtained for more than 12 months. Discussion: With respect to locoregional disease control, it has been reported that abdominoperineal resection can obtain better control of local disease in comparison to local resection. Laparoscopic surgery is advantageous in its facilitation of an early postoperative recovery for elderly patient. Conclusion: Laparoscopic abdominoperineal resection may control locoregional disease and improve the patient's QOL with early postoperative recovery. —even in septuagenarian patients—may become a treatment strategy for advanced ARMM. Highlights: Anorectal malignant melanoma is a rare disease with a poor prognosis. Surgical procedure for anorectal malignant melanoma is controversial. APR may achieve better local control for advanced anorectal malignant melanoma. Laparoscopic surgery is advantageous in its facilitation of an early recovery for elderly patient.